Leaching of Sodium Sulphide Roasted Ilmenite Sand (Bangladesh Journal of Scientific and Industrial Research, 2008)
The possibilities of co-leachings of Ti(IV) and Fe(III) from the roasted product of ilmenite sand with sodium sulphide at the optimum conditions by hydrochloric and sulphuric acid were investigated. The leaching was dependent on hydrochloric and sulphuric acid concentrations, temperature and leaching time. The optimum conditions for the best dissolution of Ti(IV) and Fe(III) were: temperature 100°C, time 60 min for 1:1 ilmenite to sodium sulphide weight ratio roasted product and 10 min for 1:2 ilmenite to sodium sulphide weight ratio roasted product, acid concentration 4-6 N and agitation speed 400 rpm. About 95 % Ti(IV) and 93 % Fe(III) dissolutions were obtained from hydrochloric acid leaching and 95 % Ti(IV) and 91 % Fe(III) were obtained from sulphuric acid leaching at a solid to liquid phase ratio (S/L) of 0.10 kg dm-3. Keywords: Ilmenite sand, Roasting of ilmenite sand, Sodium sulphide roasted ilmenite, Leaching of roasted product, Dissolution of titanium and iron. Bangladesh J. Sci. Ind. Res. 42(4), 367-376, 2007